Pembangunan Sosial di Wilayah Pesisirsebagai Komitmen Pencegahan Human Trafficking - Septiary Chandra, Pivit; Ilosa, Abdiana (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
The purpose of this research is to examine how sustainable social development can be an effective commitment to the prevention of human trafficking in coastal areas because coastal areas, with their unique demographic and economic conditions, face major challenges in addressing human exploitation, whether in forced labor, child trafficking or sexual exploitation. This qualitative research uses a literature review method that analyzes various journals, research reports, and related policies. The analysis was conducted by categorizing the findings based on key themes, such as causal factors of human trafficking, social development policies, and intervention strategies. This research emphasizes that planned and comprehensive social development can reduce the potential for human trafficking in coastal areas. Through improved economic welfare, better access to education, and improved social and economic infrastructure. Therefore, a strong commitment is needed from the government, community organizations, and local communities to implement sustainable social development strategies to create safer and more prosperous coastal areas.